SUCCESSFUL RECOVERY OF BREAST CANCER SCREENING AND DIAGNOSIS RATES DURING COVID-19 PANDEMIC BY ADOPTING THE RECOMMENDATIONS OF THE BRAZILIAN COLLEGE OF RADIOLOGISTS (CBR), THE BRAZILIAN FEDERATION OF GYNECOLOGISTS AND OBSTETRICIANS (FEBRASGO), AND THE BRAZILIAN MASTOLOGY SOCIETY (SBM): DATA FROM A PRIVATE BREAST UNIT IN BELO HORIZONTE, BRAZIL - Couto, Henrique Lia; Sá, Nayara Carvalho de; Sales, Rachel Saraiva Teatini Selim de; Oliveira, ereza Cristina Ferreira de; Bacha, Patrícia Martins Gomes El; Ferreira, Shirley das Graças; Silva Junior, Gabriel de Almeida; Valadares, Carolina Nazareth (Mastology, 2021)
Objectives: To present the results of adopting CBR/FEBRASGO/SBM recommendations for breast cancer screening and diagnosis during 2020 COVID-19 PANDEMIC on mammograms (MMG), breast ultrasound (BUS), breast biopsy (BB), and cancer diagnosis (CD) rates. Methodology: Comparing by month the total number of MMG, BUS, BB (composed of fine needle, core, and vacuum procedures), and invasive and in situ cancers diagnosis (CD) performed at Redimama, a private breast unit from Belo Horizonte Brazil, that adopted CBR/FEBRASGO/SBM recommendations for breast cancer screening and diagnosis during the 2020 COVID-19 pandemic year to 2019 same period. Results: In April 2019, 391 MMG, 714 BUS, 223 BB, and 22 CD were performed, compared with 115 (29.4%) MMG, 313 (43.8%) BUS, 116 (52%) BB, and 11 (50%) CD in 2020. A continuous and fast recovery occurred along the time. In 2019 first semester, 2241 MMG, 4229 BUS, 1214 BB, and 84 CD were performed, compared with 1,903 (88.7%) MMG, 4,227 (99.2%) BUS, 1,044 (86%) BB, and 92 (109.5%) DC in 2020. In 2019, 4,424 MMG, 10,395 BUS, 3,304 BB, and 231 CD were performed, compared with 4,561 (110.79%) MMG, 11,549 (120.72%) BUS, 3,011 (91.13%) BB, and 226 (97.83%) CD in 2020. In 2019, the median size in image (T) by MMG/BUS for invasive cancers (IC) was 18.18 mm, from CD 184 (79.66%) were IC, and 47 (20.4%) ductal carcinoma in situ (DCIS) compared to a T of 18.2 mm, 191 (86.52%) IC, and 35 DCIS in 2020. Conclusion: Adopting the CBR/FEBRASGO/SBM recommendations for breast cancer screening and diagnosis results to recovery the prior pandemic levels. Recovery of MMG and BUS is faster and shows a “J” curve compared with recovery of BB and CD that shows a “´U”` curve with a delay. This strategy should be adopted in Brazil in order to maintain breast cancer screening and diagnosis.